A Study of Anita Desai’s Novels Fire on the Mountain: Exploring the psyche of Nanda Kaul and Raka in Anita Desai's Fire on the Mountain (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In Fire on the Mountain (1977) Anita Desai depicts the psyche of Nanda Kaul, who has withdrawn herself from all movements and echoes. Initially, she had led a perturbed busy life as the Vice-Chancellor’s wife, looking after several children and grandchildren and arranging for interminable get-togethers. But now she, as a widow, is living in isolation in a secluded bungalow in Kasauli along with her male servant. She wants no contact with outside world. The other important character is that of Raka the great-granddaughter of Nanda Kaul. The novel is obviously a study of feminine sensibility about Nanda Kaul, Raka and Ila Das the bare mountainous terrain and a desert-burnt-out bungalow at hill top, which fascinates Raka, symbolizes her psychic void character which is an outcome of her emotional deprivation since she comes from from a broken home with a sick mother and an alcoholic father who beats his wife. The pathetic story of Ila Das, who fascinates as well as repels Nanda Kaul’s delicate sensibility, is faced with acute financial problems, becomes a welfare officer and is posted in the hills. Once she gives a sane advice to a villager from marrying off his seven year-old daughter to a farmer who is a widower with seven children.